Long‐term follow‐up of Norwegian horses affected with acquired equine polyneuropathy. (27th February 2017) - Hanche‐Olsen, S.; Kielland, C.; Ihler, C. F.; Hultin Jäderlund, K.
Summary: Background: Acquired equine polyneuropathy (AEP), a neurological disease clinically characterised by knuckling of metatarsophalangeal joints, has been described in numerous Nordic horses during the last 20 years. Although clinical recovery has been reported, large‐scale data on long‐term follow‐up of survivors have been lacking. Objectives: To describe long‐term survival of AEP affected horses registered in Norway, with a focus on athletic performance and possible residual clinical signs connected to the disease. Study design: A retrospective cohort study. Methods: The study includes 143 horses recorded with AEP in Norway from 2000 to 2012, with the follow‐up period continuing until 2015. Participating owners of survivors completed a standardised questionnaire, providing information on disease and convalescence, management, performance‐level and possible residual clinical signs. To investigate the follow‐up of survivors, we performed 2 multivariable linear regression models. Results: The follow‐up time of survivors was 1.0–14.5 years (median 5.3, interquartile range 2.5–7.2). Fifty‐seven horses survived and all but 3 horses returned to previous or higher level of performance. However, possible disease‐related residual clinical signs were reported in 14/57 horses. Forty‐nine of the survivors were in athletic use at time of contact. The majority of survivors were categorised with low severity‐grades at time of diagnosis and the initial grade was significantly associated with time to resumed training. Only 3 horses had experienced relapse/new attack during the follow‐up period. Main limitation: Athletic performance was judged by owners, which renders a possible source of bias. Conclusions: Although AEP is a potential fatal disease, most survivors will recover and return to minimum previous level of athletic performance. Some horses display residual clinical signs, but often without negative effect on performance and relapse of disease is rare.